2000
DOI: 10.1054/bjoc.2000.1398
|View full text |Cite
|
Sign up to set email alerts
|

Oral hygiene, dentition, sexual habits and risk of oral cancer

Abstract: In an Italian case-control study of oral cancer, number of missing teeth and other aspects of dental care were similar, but the general condition of the mouth, as indicated by gum bleeding, tartar deposits and mucosal irritation, was worse among oral cancer cases than controls. No differences were detected in sexual practices (including oral sex) and (previous) sexually transmitted infections. © 2000 Cancer Research Campaign

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
129
3
4

Year Published

2003
2003
2014
2014

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 161 publications
(153 citation statements)
references
References 15 publications
17
129
3
4
Order By: Relevance
“…79 By contrast, several case-control studies observed no significant associations between risk of oral cancer and number of sex partners, frequency of oral sex, sex with prostitutes, or a history of genital herpes or gonorrhea. [92][93][94][95][96][97] Because only a fraction of oropharyngeal cancers are likely attributable to HPV, risk estimates may be attenuated if the majority of oral or oropharyngeal cancer cases are not etiologically associated with HPV. For example, case-control studies that observed no associations with sexual behaviors in the entire study population found that number of sexual partners, oral sex, and oral-anal contact were significantly associated with HPV-positive cases.…”
Section: Sexual Behavior and Human Papillomavirus Infectionmentioning
confidence: 99%
See 1 more Smart Citation
“…79 By contrast, several case-control studies observed no significant associations between risk of oral cancer and number of sex partners, frequency of oral sex, sex with prostitutes, or a history of genital herpes or gonorrhea. [92][93][94][95][96][97] Because only a fraction of oropharyngeal cancers are likely attributable to HPV, risk estimates may be attenuated if the majority of oral or oropharyngeal cancer cases are not etiologically associated with HPV. For example, case-control studies that observed no associations with sexual behaviors in the entire study population found that number of sexual partners, oral sex, and oral-anal contact were significantly associated with HPV-positive cases.…”
Section: Sexual Behavior and Human Papillomavirus Infectionmentioning
confidence: 99%
“…28,94,95,131,132 Clinical findings consistent with poor oral hygiene on examination (eg, mucosal irritation, dental caries, tartar) were associated with a 2-to 4-fold increase in risk after adjustment for sex, age, diet, alcohol, and tobacco habits. 93,133 The strongest and most consistent indicator of risk in the literature was tooth loss, likely indicative of chronic poor oral health. Several studies reported elevated risk associated with any tooth loss 90,93,129,[134][135][136] and also increased risk with increased number of lost teeth.…”
Section: Oral Hygienementioning
confidence: 99%
“…Recently, the role of other factors, such as poor oral hygiene and dentition (Talamini et al, 2000), genetic susceptibility (Warnakulasuriya et al, 1998), sexual habits (Garrote et al, 2001) and infection by human papillomavirus (Mork et al, 2001), has been investigated.…”
mentioning
confidence: 99%
“…Lockhart et al (1998) did not find statistically significant results for association between oral cancer and dental factors, including tooth loss, defective teeth and denture use (Lockhart et al, 1998). Studies by Talamini and Rosenquist link dental status with oral cancer risk using control group randomly conformed (Talamini et al, 2000;Hansson et al, 2005).…”
Section: Discussionmentioning
confidence: 95%